From Lament to Guilt: The Beginnings of Theology in the Book of Jeremiah - Schmid, Konrad (Hebrew bible and ancient Israel, 2021)
Within the earliest texts in the book of Jeremiah, a remarkable theological development can be reconstructed: A first layer of prophetic laments seems to have been expanded by theological interpretations that imply a shift from lament to accusation. The disaster that Judah and Jerusalem experience before and after the catastrophe of 587 BCE is not a historical coincidence, but the result of a divine plan. In this development, the beginnings of theology in the book of Jeremiah can be discerned.